PENGARUH MEDIA BUKU BERGAMBAR TERHADAP MINAT BACA SISWA KELAS II SD NEGERI 101797 DELI TUA - Yurhie Kehnia; Umar Darwis (Yayasan Pendidikan Islam dan Multikultural, 2021)
This study aims to determine the effect of picture storybook media on reading interest in second grade students of SD Negeri 101797 Deli Tua. The population in this study were all second grade students, totaling 30 students. While the sample amounted to 30 students. This research is a quantitative research with the type of pre-experimental research with One Shot Case Study design. The instrument used in this research is a questionnaire. From the results of the research analysis the influence of picture book media on the reading interest of second grade students of SD Negeri 101797 Deli Tua is 0.709 which shows high results. This can be seen from the correlation between variable X (picture books) and variable Y (interest in reading).